PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI MITRA SWALAYAN PURWODADI - Gilang Adi Patandi Putra; Indah Rahayu (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2023)
Background : The rapid development of technology and information such as the current industrial scope is pushing the business environment into a disruptive era. Efforts to improve employee performance can be done through leaders who are able to provide change and provide information, which is called transformational leadership. Apart from leadership style, improving employee performance can be done by paying attention to the work environment and employee motivation so that employee performance runs optimally and satisfies the company. With this research, it is hoped that employee performance will improve in order to achieve company goals. Purpose: To determine the influence of transformational leadership on employee performance at Mitra Swalayan Purwodadi, To determine the influence of the work environment on employee performance at Mitra Swalayan Purwodadi, To determine the effect of work motivation on employee performance at Mitra Swalayan Purwodadi Methods: This research uses quantitative. Determining the sample size used the census formula with an overall sampling technique from a population of 95 respondents. Analyzed using analytical techniques Statistical Program For Social Science (SPSS 24.0 version) for windows. Conclusion: Transformational leadership, work environment, and work motivation influence and play an important role in employee performance Suggestion: It is hoped that further research will develop the variables to be studied to provide a broader relationship in the field of management, and use new methods for academic development, for example employee commitment, employee experience and employee involvement, which can help provide insight into how employees view organization, and in particular also their attitudes towards the organization.